Safety and efficacy of IIb/IIIa inhibitors in combination with highly active oral antiplatelet regimens in acute coronary syndromes: A meta-analysis of pivotal trials. (17th February 2017) - Roule, Vincent; Agueznai, Moaad; Sabatier, Rémi; Blanchart, Katrien; Lemaître, Adrien; Ardouin, Pierre; Collet, Jean-Philippe; Milliez, Paul; Montalescot, Gilles; Beygui, Farzin
Abstract: The risk and benefit of GP-IIb/IIIa Inhibition (GPI) in combination with recent antiplatelet regimens in acute coronary syndromes (ACS) remain unassessed. The advent of fast-acting highly active oral P2Y12 inhibitors questions the additional value and risk of their association with GPI. We studied the effect of GPI in combination with prasugrel and ticagrelor, compared to clopidogrel on major bleeding in pivotal randomized controlled trials in the setting of ACS, using a meta-analytic approach. A similar analysis, further including the comparison of a double versus standard dose clopidogrel regimen, was performed for the risk of the primary efficacy endpoint. The combination of GPI and recent P2Y12 inhibitors was associated with a similar risk of bleeding as compared with GPI and the standard clopidogrel regimen (RR 0.92 [0.74; 1.13]). The benefit of recent regimens, including double dose clopidogrel, in reducing the primary ischemic endpoint (RR 0.86 [0.78; 0.94]) persisted in those treated with GPI. Although GPI use was associated with a consistent increase in the risk of bleeding in both recent (RR 1.27 [1.05–1.55]) and standard regimens (RR 2.01 [1.64–2.47]), the relative magnitude of such an increase was lower in association with prasugrel or ticagrelor as compared with clopidogrel. The risk of bleeding using a combination of GPI and oral antiplatelet regimens is mainly related to the use of GPI and not the oral antiplatelet regimen. Considering the absence of increased risk of bleeding and the persistence of the benefit of recent P2Y12 regimens in combination with GPI as compared with the standard clopidogrel regimen, the use of such a combination within the guidelines is supported by our findings.